How do I solve this function?

(x-3)(x-4)

(x-5)(x-6)² =0

Printable View

- Oct 19th 2008, 07:49 PMRaphaelB30Polynomial equation
How do I solve this function?

(__x-3)(x-4)__

__(x-5)(x-6)__² =0 - Oct 19th 2008, 07:55 PMryukolink
Simple Polynomial Multiplication

first three examples are what you want to study

basically its called the FOIL method, I forgot what it means, but I know how to do it and that site shows it better than I could, for the 2nd question you want to take the

(x-6)² = (x-6)(x-6)

Then take that answer and multiply by (x-5)

Follow the sites first 3 examples and you'll be golden

*edit*

Ok I remembered, FOIL is FIRST OUTER INNER LAST, Basically you would take

(x-5)(x-6)=

First = (x)(x)

outer= (x)(-6)

Inner=(x)(-5)

LAST=(-5)(-6)

combined it gives you this : (x)(x) + (x)(-6) + (x)(-5) + (-5)(-6)

Which gives you the answer to that problem but not yours, you gotta do your problem yourself :) No fun in me doing it for you! wait, that kind of is your problem, blast!